2021
DOI: 10.47191/ijcsrr/v4-i5-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Pharmacokinetics and Pharmacodynamics of Investigational Once-Daily Sustained-Release (SR) Vildagliptin 100 mg Tablet Formulation with Conventional 50 mg Twice-Daily Regimen in Healthy Indian Males

Abstract: Background- Among the gliptins, vildagliptin is the only therapy requiring twice-daily dosing and thus adversely impacts patient adherence. To reduce dosing frequency, we developed a once-daily sustained-release (SR) vildagliptin 100 mg tablet formulation with potential to furnish comparable dipeptidyl peptidase-4 (DPP-4) inhibition coverage to the conventional twice-daily regimen. Objective- The current study compares the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of investigational once-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…7,8 As per the available data, gliptins' average DPP-4 inhibition over 24 hours must exceed 70% to demonstrate clinically significant glucose lowering benefits. 2 Additionally, it has been shown that DPP-4 inhibition of >80% increases active glucagon-like peptide-1 and gastric inhibitory polypeptide levels by 2-fold, resulting in near-maximal decreases in plasma glucose levels. 9 This study reported DPP-4 inhibition above 80% for 24 hours with both once-daily Vildagliptin SR 100 mg tablets and twice-daily Vildagliptin IR 50 mg tablets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 As per the available data, gliptins' average DPP-4 inhibition over 24 hours must exceed 70% to demonstrate clinically significant glucose lowering benefits. 2 Additionally, it has been shown that DPP-4 inhibition of >80% increases active glucagon-like peptide-1 and gastric inhibitory polypeptide levels by 2-fold, resulting in near-maximal decreases in plasma glucose levels. 9 This study reported DPP-4 inhibition above 80% for 24 hours with both once-daily Vildagliptin SR 100 mg tablets and twice-daily Vildagliptin IR 50 mg tablets.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is recommended to use Vildagliptin 50 mg twice-daily (BD) to provide ≥90% inhibition of DPP-4 over 24 hours. 2 Patients with T2D, due to the progressive nature of the disease, often require multiple oral hypoglycemic agents and add on insulin therapy as monotherapy or as part of polytherapy. A considerable amount of evidence indicates that polytherapy and multiple daily dosage schedules decrease patient adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…India’s central drug standard control organization (CDSCO) approved vildagliptin in 2008 [ 5 ]. A single dose of 50 mg vildagliptin provides ≥80% DPP4 inhibition for 12 hours; a bolus of 100 mg vildagliptin confers the same DPP4 inhibition for 15 to 16 hours [ 6 ]. When combined with metformin, pioglitazone, or insulin in T2DM, vildagliptin lowered glycated hemoglobin (HbA1c) levels [ 5 ].…”
Section: Reviewmentioning
confidence: 99%